Adaptation of the strain measurement in textile reinforced cementitious matrix composites by distributed optical fibre and 2D digital image correlation. (30th December 2019) - Saidi, M.; Gabor, A.
Abstract: The study presented in this paper aims to adapt and calibrate two strain measurement techniques used for textile reinforced cementitious matrix composites (TRCMCs): distributed optical fibres and 2D digital image correlation (DIC). These composites exhibit tensile behaviour characterised by a succession of transverse cracks along specimens. During the tensile test, out‐of‐plane parasitic displacements may occur due to the geometry of specimens and possible imperfections of the test method. These phenomena interfere with the measurement of the strain sensors, leading to loss of results and parasitic strain. In order to eliminate them and to finely analyse the complex behaviour of TRCMCs, a test methodology and experimental approach are proposed for optical fibres, and a practical and simple solution is proposed to quantify the parasitic strains of the 2D DIC. For optical fibres, Rayleigh backscatter is used, allowing a millimetric spatial resolution and a high recording frequency. For the DIC, required equipment is used, and the results are processed through existing commercial software.